2019
DOI: 10.1292/jvms.18-0550
|View full text |Cite
|
Sign up to set email alerts
|

Detection of avian encephalomyelitis virus in chickens in Japan using RT-PCR

Abstract: A reverse transcription-polymerase chain reaction (RT-PCR) method was developed for broadly detecting the avian encephalomyelitis virus (AEV). The new primers were based on conserved sequences of the 5’-untranslated region of AEV, because the virus was not detected using previous reported RT-PCR. By applying this method to the chicken samples with suspected AEV infection in Japan, we successfully obtained PCR products of the predicted size from all samples, and we confirmed the presence of AEV via sequence ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Picornaviruses are commonly identified infecting a variety of avian species in metagenomic studies. In the context of overt disease, notable avian picornaviruses include avian encephalomyelitis viruses in chickens, pheasants, and turkeys ( 80 ), duck hepatitis A in ducklings ( 81 ), and a novel poecivirus that has been identified strongly associated with avian keratin disorder (AKD) in Alaskan birds ( 82 ). We identified two novel picornaviruses in this study, Garigal virus and Cowan virus, the pathogenic potentials of which merit further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Picornaviruses are commonly identified infecting a variety of avian species in metagenomic studies. In the context of overt disease, notable avian picornaviruses include avian encephalomyelitis viruses in chickens, pheasants, and turkeys ( 80 ), duck hepatitis A in ducklings ( 81 ), and a novel poecivirus that has been identified strongly associated with avian keratin disorder (AKD) in Alaskan birds ( 82 ). We identified two novel picornaviruses in this study, Garigal virus and Cowan virus, the pathogenic potentials of which merit further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The AEV infection in poultry flocks caused severe economic losses in the poultry industry by increasing mortality and medication costs and decreasing egg production and hatchability [ 1 , 18 ]. The present cross-sectional study reported an overall 70.18% of Sonali parents’ chickens of Bogura district positive for AEV-specific antibodies during the laying period.…”
Section: Discussionmentioning
confidence: 99%
“…Picornaviruses are commonly identified infecting a variety of avian species in metagenomic studies. In the context of overt disease, notable avian picornaviruses include avian encephalomyelitis viruses in chickens, pheasants, turkeys (77), duck hepatitis A in ducklings (78), and a novel poecivirus that has been identified strongly associated with Avian keratin disorder (AKD) in Alaskan birds (79, 80). We identified two novel picornaviruses in this study - black and white bird picornavirus and a lorikeet hepatovirus - the pathogenic potential of which merits further investigation.…”
Section: Discussionmentioning
confidence: 99%